An Autopsy Study of Burn Injuries in Elderly Women - Asma Kausar1 , Dayananda R1 , Varghese P S2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Fire is mischievously called “necessary evil”. Burn injuries have long been described as among the mostserious injuries that may affect human body. The issue of burns has always been a significant cause ofmorbidity and mortality in both developing and developed countries around the world and a major cause ofglobal public health crises.1,2 A 10 year retrospective study of death in elderly burn victims was under takenat St. Johns medical college hospital, Bangalore, India. It was observed that majority of the victims werewoman, many of them sustained burns while performing “Puja” (ritual of worshipping God). All were dryburns. Face and upper part of chest was spared in 80% of cases. 80% victims sustained burns during morninghours. Total body surface area involved ranged from 50 to70%.